Working Women and the Transformation of Family Relationship Patterns in Bangladesh - Haque, Israt Eshita; Haque, Mehjabin; Muniruzzaman, Md.; Hossain, Md. Sabbir (Technium Social Sciences Journal, 2021)
The study focuses on working women and their changing forms of family relationship patterns in Bangladesh. The study was conducted from September 2020 to December 2020 to examine the socio-economic condition of working women, the transformation of family relationship patterns, and the obstacles of working women. The study was qualitative in which multiple case studies were employed. Results demonstrate that working women play a significant role as the important agents for the transformation of family patterns in Bangladesh. The results unravel the obvious outcomes of the patterns of family transformation from both functional and conflict points of view. The study observed that there are some noticeable changes within the family for working women in where some are functional including changing pattern of gender role, the transformation of family structure, modification of economic decision making, socialization of the children, and individual freedom of women. This study also elucidates some changing patterns of the family that can be considered from the conflict point of view such as, negative impact on children, fertility-related problem, conflicting intimate relationship, extramarital relationships, divorce, separation, broken family, single parents’ family, and so on. It also demonstrates a need to address some obstacles faced by working women and some potential strategies to create equilibrium within the family and workplace as well as enhancing the overall status of women in society.